Increasing profitability, yields and yield stability through sustainable crop establishment practices in the rice-wheat systems of Nepal. (July 2019) - Devkota, M.; Devkota, K.P.; Acharya, S.; McDonald, A.J.
Abstract: The rice-wheat rotation is the dominant cropping pattern in the Terai 'food basket' of Nepal. Current production practices require significant labor, water, and energy which erode profitability and, hence, incentives for intensification. Dry direct seeded rice (DSR) and zero tillage wheat (ZTW) have been widely tested on experiment stations as alternative establishment technologies in South Asia. However, adoption at the farm level is low, perhaps in part due to the absence of systematic technology assessment across production ecology gradients under 'real world' conditions. A series of participatory on-farm experiments were conducted over seven-years (2011–2017) for performance verification and refinement of DSR and ZTW technology in the western Terai region of Nepal. DSR and ZTW produced a similar or higher grain yield with lower total production cost (by 160 ha −1 in DSR and 70 ha −1 in ZTW); and higher water productivity (by 4–18% in DSR and 30% in ZTW) and net profit (by 122–232 ha −1 in DSR and 115 ha −1 in ZTW) as compared to conventional practices. When early rainfall is deficient, DSR permits timely establishment which significantly boosts yields and produced stable yield with farmers' adoption. Agronomic adjustments to DSR practices further boosted performance, with pre-sowing irrigation followed by shallow tillage reducing early weed pressure (by 30–45%) and increasing grain yield in contrast to DSR established with post-sowing irrigation. DSR can be cultivated using the same varieties and fertilizer rates as PTR, whereas ZTW can be cultivated using the same variety as conventionally tilled wheat, but fertilizer rates should be adjusted. When adopted in tandem, results confirm that DSR followed by ZTW increased rice-wheat system productivity by 0.5 to 1.9 t ha −1, reduced total production cost by 237 ha −1, and increased net profit by 347–572 ha −1 and minimized the climatic risk compared to conventional practices in rainfed or limited irrigation areas. While the benefits are clear, coordinated efforts are required to overcome technology scaling bottlenecks that have kept adoption rates of these technologies at a nascent state in Nepal. Highlights: DSR-ZTW system reduces production costs, increase net return, and minimize climatic risk. Pre-sowing irrigation followed by shallow tillage minimize risks in DSR by reducing weed pressure. DSR can be grown using the same variety and fertilizer rate as with conventional practices. ZTW enables earlier planting, which can lead to higher yields Crop management is the impetus for the wider promotion and adoption of DSR.